Panal que cela su oro: (auto)censura, traducción, cartas y versos de amor de Gabriela Mistral a Doris Dana y a Paulita Brook - Elena Madrigal; Sulemi Bermúdez Callejas (L'Ordinaire des Amériques)
We analyze Gabriela Mistral’s ethos from a queer feminist standpoint. We rely on her diaries, the love epistles she addressed to Doris Dana, and the “La dichosa” poem, dedicated to Paulita Brook. Our approach reveals a multifarious ethos, one that oscillates between her public repute and her discreet albeit dissident lesbianism. Following recent scopes to study Mistral’s legacy, we propose a three-fold perspective to delve into her ethos: Mistral’s iconic configuration as promoter of women’s rights, the (self) censorship that surrounded her persona, and a fresh reading of one of her poems. By taking into consideration some biographical and contextual touchstones –and against reductionist approaches– we argue that the acceptance of Mistral’s sexual orientation allows for new interpretations of her writing and for the comprehension of the partial translations of her oeuvre into English, as well as the late publication of her complete works.